Pre-hospital emergency cricothyrotomy in dogs part 2: Airway sealing and ventilation using cricothyrotomy tubes - Hardjo, Sureiyan; Haworth, Mark; Croton, Catriona; Purcell, Sarah; Goodwin, Wendy (Frontiers in Veterinary Science, 2023)
Cricothyrotomy (CTT) has been recommended for use in the pre-hospital setting for military working dogs and Operational K9s during airway emergencies. Although the CTT can establish a patent airway, the ability to seal the airway and provide positive pressure ventilation (PPV) using tubes designed for humans has not been determined. Using various CTT tubes placed in cadaver dog airways, we sought to determine: (1) Whether the tube cuff could create a functional airway seal with safe intra-cuff pressures; (2) The magnitude of delivered tidal volume (TV) loss during a standard breath to assess the possibility of delivering an adequate tidal volume with a bag-valve device (BVM); (3) The best performing tubes for either test; (4) The reasons behind our findings using observations from upper airway endoscopy, dissection, and measurements. Cadaver dogs of similar weights to MWD and Operational K9 breeds had various CTT tubes placed including three from commercial kits, a standard endotracheal tube, and a tracheostomy tube. The minimum occlusive volume (MOV) technique was used to inflate the tube cuff and a pressure ≤ 48 cm H2O with an adequate seal was considered successful. Individual TVs were calculated for each dog and added to the volume lost during delivery of a standard breath from an ICU ventilator. Endoscopy and airway dissection were performed to assess the relationship between tubes cuffs and the airway. The tubes from the CTT kits performed poorly with regards to producing an airway seal with the H&H tube failing to seal the airway all tests. Tracheal dimensions were significantly associated with successful airway sealing (P=0.006). Tidal volume loss could be compensated using a BVM in 34/35 tests with the H&H tube in cadaver 8 the only to fail. Tracheal airway sealing is influenced by airway anatomy when tube cuffs are inflated to a target pressure and larger tubes do not always provide a better seal. The CTT tubes tested have the potential to facilitate ventilation with a BVM under the conditions set in this study. The 8.0 mm endotracheal tube performed the best and the H&H the worst in both tests.